PEMODELAN DAN SIMULASI KINERJA PIN UJI BAHAN BAKAR PWR DENGAN UO2 DIPERKAYA - Mutiara, Etty; Yulianto, Tri; Dewayatna, Winter (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Modeling and simulation of irradiation of PWR type test fuel of mini pin in RSG GAS reactor has been done using thermomechanics computer code of FEMAXI-6. The simulation was conducted by varying fuel enrichment under irradiation to predict fuel performance. The expected result from the simulation is the availability of simulation data on fuel behavior under simulated irradiation with different enrichment, neutron fluxes along the fuel, length of time and burn-up level at the beginning of contact between fuel pellets and cladding (Pellet-Cladding Mechanical Interaction,PCMI). The simulation data will provide valuable information for real irradiation experiment planning in RSG GAS reactor. The input for the simulation includes geometry and materials and operation condition such as neutron fluxes and linear heat rate. The calculations include heat generated by the fuel, heat transferred out of the fuel, axial and radial distribution of temperatures along the fuel, fission gas release and also pressure generated in fuel pin for whole length of the fuel pin. Temperature distribution calculation from thermal analysis module is applied to detailed mechanical analysis module to calculate gap width between the pellet and the cladding. The simulation shows a trend for reduction of contact time between fuel and cladding with increasing enrichment level at a same reactor power level because higher enrichment will cause higher linear heat rate. While PCMI does not occur on natural uranium fuel even for 100% burnup at full power level, fuel pin containing 5% enriched uranium causes the occurance PCMI at 900 hours of irradiation despite a reduce of power level by half with only 4% burnup.